Bayesian estimation of reliability - Rahmi, Depriwana (2005)
Most of statistical theory thought at the undergraduate level is based on classical probability or frequentist probability. Also, the estimation techniques widely used are maximum likelihood estimation (MLE) and methods of moment. This dissertation discusses the subjective probability as an alternative theory, where Bayesian estimation is used. Based on a random sample of 20 observations that was generated from Weibull distribution, we compare the reliability estimation using MLE and Bayesian approach. We found out that the mean percentage error for Bayesian is 7.9678, which is lower than MLE mean percentage error of 10.8434. Thus, bayesian reliability estimation is better.